ORGANIC AGRICULTURE IN BRAZIL WITH A FOCUS ON BIODYNAMIC AGRICULTURE - Leite, Andressa Beatriz; Polli, Henrique Quero (Revista Interface Tecnológica, 2020)
The use of pesticides in Brazil is high, and its application is often done incorrectly. From 1920, movements against the use of chemical fertilizers started to appear, in this context organic agriculture arises. There is no doubt about the increased interest on the part of the consumer who has been looking for food without pesticides, coming from a system that respects the environment. Organic agriculture can be defined as a set of agricultural production processes, based on the assumption that fertility is a direct function of the organic matter contained in the soil, and within these alternative methods, biodynamic agriculture is inserted, a current that appeared in a cycle of eight lectures given in Poland by the philosopher Rudolf Steiner, arguing that the health of the soil, plants and animals depends on their connection with the forces of nature's cosmic origin. This article aims to analyze biodynamic agriculture in Brazil, verifying the advantages and benefits of this current of organic agriculture, as well as the methods used by this segment.